2022
DOI: 10.1186/s40794-022-00169-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of dengue and SARS-COV-2 co-infection in an endemic area of Colombia

Abstract: Since the COVID-19 outbreak, millions of people have been infected with SARS-CoV-2 around the world. An area of epidemiological relevance is Latin America, tropical regions, due to the distribution of endemic diseases such as chikungunya, dengue (DENV), malaria, Zika virus, where febrile disease abounds. The early signs and symptoms of DENV and COVID-19 could be similar, making it a risk that patients may be wrongly diagnosed early during the disease. The problem increases since COVID-19 infection can lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Without field studies for direct case detection coincident with ecological studies, it is impossible to identify the full swath of variables that define transmission in specific contexts. Finally, this study was during the pandemic lockdown in Colombia and epidemiological behavior might not be indicative of “normal” [ 65 , 66 ] and declining cases were reported in some places [ 67 , 68 ] as well as a COVID-related potential for misdiagnosis [ 69 , 70 ]. The SARS-CoV-2 pandemic arrested much activity in Colombia in the middle of sampling time.…”
Section: Discussionmentioning
confidence: 99%
“…Without field studies for direct case detection coincident with ecological studies, it is impossible to identify the full swath of variables that define transmission in specific contexts. Finally, this study was during the pandemic lockdown in Colombia and epidemiological behavior might not be indicative of “normal” [ 65 , 66 ] and declining cases were reported in some places [ 67 , 68 ] as well as a COVID-related potential for misdiagnosis [ 69 , 70 ]. The SARS-CoV-2 pandemic arrested much activity in Colombia in the middle of sampling time.…”
Section: Discussionmentioning
confidence: 99%
“…Initial differentiation between dengue and COVID-19 is a challenge as both infections have similar symptoms, such as fever, diarrhea, myalgia, and headache, and these overlap [ 64 , 65 ]. However, studies suggested that SARS-CoV-2 and DENV coinfection had less severe symptoms compared to isolated monoinfection [ 13 ]. Tropical countries, especially those with endemic DENV, approached a syndemic state, because multiple patients were coinfected with both SARS-CoV-2 and DENV.…”
Section: Sars-cov-2 and Dengue Coinfectionmentioning
confidence: 99%
“…COVID-19 can be misdiagnosed with dengue. This situation complicates matters, so it can be difficult to distinguish between early infections and coinfections, generating an important risk for the population and demanding greater attention from health systems, because both viruses can cause serious complications, mainly through the cytokine storm in lung tissue caused by macrophage hyperactivation [ 13 , 27 , 64 ].…”
Section: Sars-cov-2 and Dengue Coinfectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this area, cases of coinfection with more severe conditions have been reported that require a stay in intensive care units and even lead to death. A recent systematic review demonstrated serious and fatal cases with COVID-19 and Dengue coinfection, with cases reported in South America, Europe, and Asia [ [2] , [3] , [4] ].…”
mentioning
confidence: 99%